An ensemble learning algorithm for optimization of spark ignition engine performance fuelled with methane/hydrogen blends - Tayarani-N., Mohammad-H.; Paykani, Amin (Applied soft computing, 2025)
The increasing global demand for sustainable and cleaner transportation has led to extensive research on alternative fuels for Internal Combustion (IC) engines. One promising option is the utilization of methane/hydrogen blends in Spark-Ignition (SI) engines due to their potential to reduce Green House Gas (GHG) emissions and improve engine performance. However, the optimal operation of such an engine is challenging due to the interdependence of multiple conflicting objectives, including Brake Mean Effective Pressure (BMEP), Brake Specific Fuel Consumption (BSFC), and nitrogen oxide (NOx) emissions. This paper proposes an evolutionary optimization algorithm that employs a surrogate model as a fitness function to optimize methane/hydrogen SI engine performance and emissions. To create the surrogate model, we propose a novel ensemble learning algorithm that consists of several base learners. This paper employs ten different learning algorithms diversified via the Wagging method to create a pool of base-learner algorithms. This paper proposes a combinatorial evolutionary pruning algorithm to select an optimal subset of learning algorithms from a pool of base learners for the final ensemble algorithm. Once the base learners are designed, they are incorporated into an ensemble, where their outputs are aggregated using a weighted voting scheme. The weights of these base learners are optimized through a gradient descent algorithm. However, when optimizing a problem using surrogate models, the fitness function is subject to approximation uncertainty. To address this issue, this paper introduces an uncertainty reduction algorithm that performs averaging within a sphere around each solution. Experiments are performed to compare the proposed ensemble learning algorithm to the classical learning algorithms and state-of-the-art ensemble algorithms. Also, the proposed smoothing algorithm is compared with the state-of-the-art evolutionary algorithms. Experimental studies suggest that the proposed algorithms outperform the existing algorithms. •An ensemble learning algorithm is proposed to build a surrogate model of a methane/hydrogen spark ignition engine performance.•Evolutionary algorithms are used to design a wagging algorithm and create the base learners.•A combinatorial evolutionary algorithm is presented to find the optimal sef of base learners.•An uncertainty reduction algorithm in evolutionary algorithms is proposed for the optimization process.•Evolutionary Algorithms are employed to optimize the engine parameters via the surrogate model.